Population-Based Trends in Invasive Prenatal Diagnosis for Ultrasound-Based Indications: Two Decades of Change From 1994 to 2016. Issue 9 (September 2019) - Lostchuck, E.; Poulton, A.; Halliday, J.; Hui, L.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2019;53:503–511) Ultrasound examination, particularly the midtrimester morphology scan, and fetal chromosome analysis provide opportunities for specialist assessment, genetic testing, and perinatal management of pregnancies complicated by fetal anomalies. Advances such as fetal nuchal translucency measurement as part of the combined first-trimester screening (CFTS) test for trisomies 21, 13, and 18; maternal plasma cell-free (cf) DNA-based screening for common aneuploidies; and prenatal diagnosis with chromosomal microarray (CMA) analysis have helped further genetic testing of fetal anomalies.